Preparation and characterization of ZnO/graphene/graphene oxide/multi-walled carbon nanotube composite aerogels - Shen, Yang; Yuan, Zhihao; Cheng, Fengjiao; Cui, Zhen; Ma, Deming; Bai, Yueyue; Zhao, Shuqing; Deng, Jieyao; Li, Enling (Frontiers in Chemistry, 2022)
ZnO/Graphene (G)/Graphene Oxide (GO)/Multi-walled Carbon Nanotube (MCNT) composite aerogels with a three-dimensional porous structure were prepared by the sol-gel method under average temperature and alkaline conditions, combined with freeze-drying process and heat treatment process. The photocatalytic degradation of Rhoda mine B (RhB) was mainly studied. The scanning electron microscope (SEM) test results showed that the morphology uniformity of the ZnO/G/GO/MCNT composite aerogel was significantly enhanced, which effectively solved the agglomeration problem of MCNT and ZnO. The UV-Vis spectroscopy test showed that the visible light response range of the ZnO/G/GO/MCNT composite aerogel was increased to 10.7%. The photocatalytic degradation test results of RhB show that due to the synergistic effect of physical adsorption and photocatalytic degradation, and the total degradation rate of RhB by ZnO/G/GO/MCNT could reach 86.8%, which is 3.3 times that of ZnO. In addition, the synergistic effect of ZnO and G effectively hinders the recombination of photo generated electron-hole pairs and enhances photocatalytic activity. The ZnO/G/GO/MCNT composite aerogel can be applied in the visible light catalytic degradation of water pollution.